Public Service Performance Analysis using Servqual Method in Bandar Pasir Mandoge Village - Rahmadhani, Dhea; Ramdhan, William; Syaputra, Abdul Karim (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Improving service in an agency cannot be separated from several aspects that must be possessed, such as assurance, empathy, responsiveness, reliability and physical evidence. However, there are several obstacles in improving services at the Bandar Pasir Mandoge Village Head's Office, such as lack of information and transparency. The aim of this research is to create a decision support system using the servqual method to improve the quality of public service performance. This research applies the waterfall model to build a system with stages of analysis, design, implementation and testing. Analysis is carried out to find needs regarding the system being created. Meanwhile, the design consists of entity relationship diagrams and interface design. Next, the implementation stage was carried out at the Bandar Pasir Mandoge Village Head Office using 201 questionnaires. The aspects in this research consist of concern, physical service, responsiveness, physical reliability, and guarantee. System testing uses a black box to see the extent of the functionality of this system. Our findings are that improvements need to be made to guarantee services (communication, courtesy, communication and security). Apart from that, our system is also running well based on the results of black box testing. So this system can be used by the Bandar Pasir Mandoge Village Head's Office as a policy in making decisions to improve the performance of public services.